Optimizing the Method and Source of Phosphatic Nutrition for Wheat (Triticum astivum L.) Under Agro-Climate of Dera Ghazi Khan, Pakistan - Maqbool, M. Mudassar; Ahmad, Maqbool; Ali, Anser; Mehmood, Rashid; Ahmad, Muhammad; Sarwar, Muhammad (Pakistan Journal of Nutrition, 2012)
In agricultural system, the application of Phosphorous (P) to the soil is essential to make sure the crop productivity as the recovery of applied P by crops becomes very low during growth period. The way, phosphorus is applied is also critical in wheat growth and development. For this purpose a field experiment was conducted to study the effect of different P fertilizers and their methods of application on wheat growth and yield. Different Phosphorus fertilizers Mono-Ammonium Phosphate (MAP), Di-ammonium Phosphate (DAP) and Triple Super Phosphate (TSP) @ 100 kg ha-1 were applied through: broadcasting, application with the seed, application 5 cm to the right and left of the seed and 5 cm below the seed. The effects of MAP, DAP and TSP on the characteristics examined was non-significant. However, effects of application methods on plant height, the number of plants m-2, biological and grain yield were found to be highly significant. The maximum grain yield was obtained from application of phosphorus 5 cm below the seed as compare with any other method. It was concluded that the method of P application 5 cm below the seed is successful agro-technique to improve and sustain the wheat growth.